Developing Project-based digital teaching materials to enhance explanatory text writing skills among senior high school students - Herzon Deostian; Nafri Yanti; Rio Kurniawan (Journal of Educational Management and Instruction (JEMIN), 2026)
The integration of digital technology into language education has created opportunities to develop more interactive and student-centered learning resources. However, existing teaching materials for explanatory text writing often remain text-oriented, lack interactivity, and provide limited support for developing students’ writing competence in accordance with the Merdeka Curriculum. This study aimed to develop and evaluate Project-Based Learning (PjBL)-based digital teaching materials for improving explanatory text writing skills among eleventh-grade senior high school students. The study employed a Research and Development (R&D) approach using the ADDIE model, consisting of analysis, design, development, implementation, and evaluation stages. The participants included 30 eleventh-grade students at a public senior high school in Bengkulu, Indonesia. Data were collected through documentation, observations, questionnaires, expert validation, and writing tests, and were analyzed using descriptive statistics and normalized gain (N-gain) analysis. The developed digital teaching materials integrated interactive features such as Heyzine Flipbook, QR codes, Padlet, videos, and project-based learning activities. Expert validation results indicated that the materials were highly feasible in terms of content, language, and design quality. The effectiveness test revealed a substantial improvement in students’ explanatory writing performance, with the mean score increasing from 65.6 in the pretest to 87.2 in the posttest and an N-gain score of 0.63, indicating moderate effectiveness. These findings suggest that PjBL-based digital teaching materials can serve as an effective instructional resource for enhancing students’ writing skills and promoting more engaging digital learning experiences.